NUMERICAL SIMULATION OF ARMOURED FIGHTING VEHICLE SUBSYSTEM TO COMPLY TO NATOâs STANAG 4569 LEVEL III - Reni
Numerical simulation of blast loading using subsystem scale of armoured fighting vehicle was carried out to increase its protection level from level 2 to 3 according to NATO’s STANAG 4569. The add on sandwich structure with aluminium foam core known as a good energy absorber is used for blast resistant structure to increase the resistance of armoured fighting vehicle against blast. The configuration of V-shaped structure as another alternative on handling the blast energy on structure was applied in this study. Numerical simulation was carried out to compare the resistance of structure against blast among the floor subsystem with monolithic floor (single plate), flat shaped and V-shaped aluminium foam sandwich structure. The simple blast model, CONWEP based on empiric blast pressure distribution and by modeling high explosive material as a continuum using Smoothed Particle Hydrodynamics (SPH) was used to model the explosion of high explosive material. Validation showed the ability of these models to represent the blast load. Validation was also carried out using experiment data from literature. Results shown that CONWEP model was able to predict acceleration value close with the experimental data of an explosion of 60gr TNT at scaled distance Z = 1.28 with difference value of 1.034% while for the SPH model, the difference value is 586.72%. For an explosion of TNT-equivalent mass of 8kg at scaled distance Z = 0.385, the CONWEP model predicted the deflection value with a difference value of 90.67% of the experimental data so that it cannot represent the failure modes of the structure. Conversely, the SPH model predicted the deflection value that matches the experimental data, with difference value of 1.33% and was able to represent failure modes of structure as happened in the experiment. Configuration of sandwich structure with flat and V shaped aluminum foam were able to withstand blast load level 3 of NATO’s STANAG 4569 and V-shaped configuration gave the best results, with maximum deflection and acceleration values of 0.125m and 24500G respectively and with the additional mass of vehicles of 251.29kg.